Preferred characterization of orbital infection (cellulitis) with exposure dose and relative medication - Omer, Mohammed Ahmed Ali (International Journal of Research in Medical Sciences, 2019)
Background: A retrospective study presenting the endemic orbital infection (cellulitis) that breakout during dusty storm season; aiming to ascertain and showing the precedence of MRI for diagnosis of orbital infection rather than CT and revealing the diagnostic abilities of cross-sectional matrices spectrum. Methods: Based on retrospective collection of diagnostics (CT and MRI) information for randomly selected patients with cellulitis and the targeting the relevant data (image interpretation, exposure dose (DLP and CTDIvol), age, BMI and matrix cross-section spectrum findings). Results: The exposure dose of orbital CT exam was 59.4 (mGy) as CT dose index (CTDIvol) and 917.3 (mGy/cm) as dose length product (DLP) that increase by increment of age and BMI. The obese patients only exposed to dose exceeding the National Diagnostic Reference by 2.8%. MRI confirmed the inflammation around the optic nerve and extension to posterio-inferior portion of the globe and affecting the optic nerve with left sided proptosis (0.5cm) better than CT. The cross-sectional matrix successfully revealed that: the Lt optic nerve’s gray value (density) increases by a factor of 17.7 (a u) and enlarged by 5 pixels greater than the Rt optic nerve. Thickening, rough surface increased gray value by 30.5 (a u), muco-thickening and choncheal enlargement at the medial boarder of Lt orbit as 10.0 pixel and Lt eye ball enlarged by a factor of 10.9 pixels. Conclusions: MRI wisely diagnose orbital infection with more details and overcoming patient radiation exposure and usage of image spectrum gives detailed characterization of lesion morphology.